2015
DOI: 10.1007/s10608-015-9727-z
|View full text |Cite
|
Sign up to set email alerts
|

The Interactive Effects of the Capability for Suicide and Major Depressive Episodes on Suicidal Behavior in a Military Sample

Abstract: Major depressive symptoms represent a significant risk for suicidal ideation and behavior. Given that suicide is fearsome, the interpersonal theory of suicide proposes that individuals who engage in suicidal behavior possess not only the desire to die, but also the acquired capability (AC) for suicide. This study examined whether major depressive episodes (MDEs) may be particularly relevant to suicidal behavior when considered in the context of AC. History of MDEs, AC, and suicide attempt history were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…However, five studies used either a small number of items or a single item from the ACSS that the researcher/s had selected, or they used the short form of the ACSS. For example, Chu et al [ 62 ] used a four-item version of the ACSS, Smith et al [ 63 ] used an eight-item version, Blankenship [ 64 ] used the single ACSS item “I am not at all afraid to die”, and Wolford-Clevenger et al [ 65 ] used the short form of the ACSS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, five studies used either a small number of items or a single item from the ACSS that the researcher/s had selected, or they used the short form of the ACSS. For example, Chu et al [ 62 ] used a four-item version of the ACSS, Smith et al [ 63 ] used an eight-item version, Blankenship [ 64 ] used the single ACSS item “I am not at all afraid to die”, and Wolford-Clevenger et al [ 65 ] used the short form of the ACSS.…”
Section: Resultsmentioning
confidence: 99%
“…Studies with larger samples often used community health datasets not primarily designed for suicide research as data (see [ 71 75 ]). Only seven studies reported conducting a priori power analyses to determine required sample (see [ 62 , 64 , 65 , 76 79 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though it was not feasible to obtain information regarding when the clinical assessments were completed in relation to the time of the present study, research has provided support for using chart diagnostic information in research studies conducted at a later point in time (e.g., Fennig, Craig, Tanenberg-Karant, & Bromet, 1994; Joiner & Lonigan, 2000; Lonigan, Carey, & Finch, 1994). Studies have also supported this methodology in military contexts (e.g., Chu et al, 2016; Hom et al, 2016)…”
Section: Methodsmentioning
confidence: 97%
“…Results indicated that being sad or hopeless was positively associated with attempted suicide. Studies examining depression and acquired capability provided support for the moderating effects of capability in the relationship between depression and suicide attempts among adult samples (Chu et al, 2016; Ferriman et al, 2020); however, the evidence for adolescents is limited. There is still much more to know regarding the antecedents, the characteristics, and the contextual factors of adolescents who attempt suicide.…”
Section: Discussionmentioning
confidence: 99%